Infrastructures and gender. FEIL 2009 analysis municipal population and autonomous communities - Gloria Alarcón García; Carolina Arias Burgos; José Colino Sueiras (Investigaciones Feministas, 2012)
The aim of this paper is to make a mainstreaming exercise in a relevant public expenses program - the General Government Fund for Local Investment in 2009- and to evidence the need for incorporating the gender perspective in each and every public policy, including those that are apparently neutral with respect to the well-being of men and women, such as those infrastructures that are usually considered to be ruled by the principal of a universally beneficiary population.